2014
DOI: 10.15740/has/irjaes/5.2/278-283
|View full text |Cite
|
Sign up to set email alerts
|

Economic of production and marketing of mango in Gadchiroli district of Maharastra

Abstract: The present study was undertaken to know the cost and returns, producers' share in consumer's rupee and problem in production and processing of mango. The study has been undertaken in Gadchiroli district. Data pertained for the year 2010-11.The standard cost concept was used for working out per hectare cost and returns. Marketing aspect was studied by calculating producers' share in consumer's rupee. Per hectare establishment cost of mango orchard during five year for overall age groups of orchard was Rs.41,79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Small and medium mango growers have perceived exploitation by middlemen as 3 rd major constraint but the large farmers perceived distant market for mangoes and high cost of transportation as 3 rd major constraint (Table 1). Earlier studies among mango growers have shown that lack of storage facilities, high cost of transportation and price fluctuation were some problems associated with marketing (Vijay et al, 2019;Datarkar et al, 2014) whereas, price fluctuation and distant market were major constraints faced by vegetable grower (Chandran & Podikunju, 2021;Singh & Hansra, 2021). Non-availability of storage, high transport cost and price fluctuation were the three major problems in Nadia district (Sarkar et al, 2018) and the existence of middlemen and lack of proper market were major marketing constraints as perceived by orange growers (Roy et al, 2018).…”
Section: Constraints In Marketing Of Mangoesmentioning
confidence: 99%
“…Small and medium mango growers have perceived exploitation by middlemen as 3 rd major constraint but the large farmers perceived distant market for mangoes and high cost of transportation as 3 rd major constraint (Table 1). Earlier studies among mango growers have shown that lack of storage facilities, high cost of transportation and price fluctuation were some problems associated with marketing (Vijay et al, 2019;Datarkar et al, 2014) whereas, price fluctuation and distant market were major constraints faced by vegetable grower (Chandran & Podikunju, 2021;Singh & Hansra, 2021). Non-availability of storage, high transport cost and price fluctuation were the three major problems in Nadia district (Sarkar et al, 2018) and the existence of middlemen and lack of proper market were major marketing constraints as perceived by orange growers (Roy et al, 2018).…”
Section: Constraints In Marketing Of Mangoesmentioning
confidence: 99%
“…Mango is effective to prevent prostate and skin cancers (Gopalakrishnan, 2013). Mango is the fifth most widely produced fruit in the world after banana, citrus, grape, and apple (Datarkar et al, 2014). It is believed that mango is originated from South East Asia and more than 1000 varieties have been identified all over the world (Rymbai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%